Protein tyrosine phosphatase N2 regulates TNFα-induced signalling and cytokine secretion in human intestinal epithelial cells. Issue 2 (29th November 2010) - Scharl, Michael; McCole, Declan F; Weber, Achim; Vavricka, Stephan R; Frei, Pascal; Kellermeier, Silvia; Pesch, Theresa; Fried, Michael; Rogler, Gerhard
Abstract : Objective: The Crohn's disease (CD) susceptibility gene, protein tyrosine phosphatase N2 (PTPN2), regulates interferon γ (IFNγ)-induced signalling and epithelial barrier function in T84 intestinal epithelial cells (IECs). The aim of this study was to investigate whether PTPN2 is also regulated by tumour necrosis factor α (TNFα) and if PTPN2 controls TNFα-induced signalling and effects in IECs. Methods: T84 IECs were used for all cell studies. Protein levels were assessed by western blotting, mRNA levels by reverse transcription–PCR (RT–PCR) and cytokine levels by ELISA. PTPN2 knock-down was induced by small interfering RNA (siRNA). Imaging was performed by immunohistochemistry or immunofluorescence. Results: TNFα treatment elevated PTPN2 mRNA as well as nuclear and cytoplasmic protein levels and caused cytoplasmic accumulation of PTPN2. Biopsy specimens from patients with active CD showed strong immunohistochemical PTPN2 staining in the epithelium, whereas samples from patients with CD in remission featured PTPN2 levels similar to controls without inflammatory bowel disease (IBD). Though samples from patients with active ulcerative colitis (UC) revealed more PTPN2 protein than non-IBD patients and patients with UC in remission, their PTPN2 expression was lower than in active CD. Samples from patients with CD in remission and responding to anti-TNF treatment also showed PTPN2 levels that were similar to those in control patients. Pharmacological inhibition of nuclear factor-κB (NF-κB) by BMS-345541 prevented the TNFα-induced rise in PTPN2 protein, independent of apoptotic events. PTPN2 knock-down revealed that the phosphatase regulates TNFα-induced extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 phosphorylation, without affecting c-Jun N-terminal kinase (JNK), inhibitor of κB (IκB) or NF-κB phosphorylation. Loss of PTPN2 potentiated TNFα-induced secretion of interleukin 6 (IL-6) and IL-8. In TNFα- and IFNγ-co-treated cells, loss of PTPN2 enhanced protein expression of inducible nitric oxide synthase (iNOS). Conclusions: TNFα induces PTPN2 expression in IECs. Loss of PTPN2 promotes TNFα-induced mitogen-activated protein kinase signalling and the induction of inflammatory mediators. These data indicate that PTPN2 activity could play a crucial role in the establishment of chronic inflammatory conditions in the intestine, such as CD.